Elevated circulating tissue inhibitor of metalloproteinase 1 (TIMP‐1) levels are associated with neuroendocrine differentiation in castration resistant prostate cancer. Issue 6 (5th January 2015) - Gong, Yixuan; Chippada‐Venkata, Uma D.; Galsky, Matthew D.; Huang, Jiaoti; Oh, William K.
Abstract : BACKGROUND: Tissue inhibitor of metalloproteinase‐1 (TIMP‐1) is a 28.5 kDa secreted glycoprotein that inhibits matrix metalloproteinase (MMP) activity. Our group has previously shown that elevated plasma TIMP‐1 levels predict poor survival in metastatic castration‐resistant prostate cancer (CRPC) patients; however, the underlying source and impact of elevated circulating TIMP‐1 protein is unknown. METHODS: In this study, we used qRT‐PCR, ELISA and immunohistochemistry to evaluate TIMP‐1 expression in androgen‐sensitive and resistant prostate cancer (PC) cell lines, tumor tissues and patient sera, and to correlate TIMP‐1 levels to expression of chromogranin A (CGA), an established marker of neuroendocrine differentiation (NED). We also explored the relationship between TIMP‐1 overexpression and induction of NED by overexpressing TIMP‐1 in androgen‐sensitive LNCaP cells, as well as by inducing NED of LNCaP cells with IL‐6. RESULTS: Patients with CRPC have significantly higher serum TIMP‐1 levels compared to patients with hormone‐sensitive disease. Although circulating TIMP‐1 levels were increased, peripheral blood cells were not the source of elevation. Instead, elevated TIMP‐1 expression was associated with higher expression of CGA in both blood and metastatic tumor tissue. We further show that androgen receptor (AR) and PSA non‐expressing prostate cancer cell lines known to display NED phenotypes such as PC‐3, PC‐3M, and DU145 cells, expressed high levels of TIMP‐1, in contrast to AR (+) and PSA (+) adenocarcinoma cell lines such as LNCaP, VCaP, and LAPC‐4, which had barely detectable levels of TIMP‐1. In addition, ectopic overexpression of TIMP‐1 in LNCaP cells did not induce NED. However, TIMP‐1 mRNA expression was elevated >10‐fold during IL‐6‐induced NED of LNCaP cells, suggesting that TIMP‐1 overexpression accompanies, but is not the driving force for NED. Finally, we show that conditioned media from androgen‐resistant PC‐3, PC‐3M, and DU145 cells induced TIMP‐1 mRNA expression in primary prostate stromal fibroblasts in an ERK and NF‐κB dependent manner. CONCLUSIONS: We provide in vitro and clinical evidence to support the association between NED and elevated circulating TIMP‐1 expression in CRPC. Our observation supports further evaluation of TIMP‐1 as a tissue and serum biomarker for NED in CRPC. Prostate 75: 616–627, 2015 . © 2015 Wiley Periodicals, Inc.